The Early Iron Age cemetery of Veliki Nerajec near Dragatuš in Bela krajina - Škvor Jernejčič, Brina (Arheološki vestnik, 2011)
In the article the results of archival research into the Early Iron Age cemetery of Veliki Nerajec near Dragatuš in Bela krajina are presented. The cemetery was excavated in the years 1900, 1901 and 1903 by Jernej Pečnik, and the material from all three excavations was sent to the Natural History Museum in Vienna (Naturhistorisches Museum Wien). A detailed revision of the material as well as archival sources has shown that an error was made when inventorizing the material from the so-called large tumulus, excavated in 1900, and thirty graves, excavated in 1903. The material from both excavations was in fact attributed only to the large tumulus, while reports of Pečnik’s third excavation campaign in 1903 have remained overlooked till now.